2006
DOI: 10.1016/j.molcel.2006.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Sister Chromatid Cohesion at the S. cerevisiae Replication Fork

Abstract: Bre1, a conserved E3 ubiquitin ligase in Saccharomyces cerevisiae, together with its interacting partner Lge1, are responsible for histone H2B monoubiquitination, which regulates transcription, DNA replication, and DNA damage response and repair, ensuring the structural integrity of the genome. Deletion of BRE1 or LGE1 also results in whole chromosome instability. We discovered a novel role for Bre1, Lge1 and H2Bub1 in chromosome segregation and sister chromatid cohesion. Bre1's function in G1 and S phases con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
340
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(359 citation statements)
references
References 41 publications
12
340
5
Order By: Relevance
“…29,30 These proteins locali�e to replication forks, at least when cells are arrested in early S phase by hydroxy urea (HU) treatment. 7 We confirmed that Ino80 and Arp8 are specifically enriched at an active replication origin, ARS607, but not at a late-firing origin, ARS609, under similar conditions ( Fig. 4A and B, Supplementary Fig.…”
Section: Ino80 Complex In Sister Chromatid Cohesion Chromosome XV Andsupporting
confidence: 74%
See 2 more Smart Citations
“…29,30 These proteins locali�e to replication forks, at least when cells are arrested in early S phase by hydroxy urea (HU) treatment. 7 We confirmed that Ino80 and Arp8 are specifically enriched at an active replication origin, ARS607, but not at a late-firing origin, ARS609, under similar conditions ( Fig. 4A and B, Supplementary Fig.…”
Section: Ino80 Complex In Sister Chromatid Cohesion Chromosome XV Andsupporting
confidence: 74%
“…Ctf18 is part of the alternative RFC complex that can both load and unload PCNA from DNA in vitro. 31,32 Since PCNA binding around the early replication origin ARS607 is reported to be significantly weaker in HU-arrested ctf18 cells, 7 we expected that PCNA binding to ARS607 would be decreased in the arp8 mutant. To our surprise, PCNA accumulated rather than decreased near ARS607 in arp8 cells (Fig.…”
Section: Ino80 Complex In Sister Chromatid Cohesion Chromosome XV Andmentioning
confidence: 98%
See 1 more Smart Citation
“…GAL-CDC20 was integrated into leu2:KAN using plasmid p453-GAL-CDC20 (ref. 54; a gift from F. Uhlmann). Strain GAL-CDH1-m11 was constructed in two steps, disruption of TRP1 by KAN and integration of GAL-CDH1-m11 into trp1:KAN 26 (a gift from W. Zachariae).…”
Section: Methodsmentioning
confidence: 99%
“…One model predicts that cohesin permits replication fork passage through the inside of its ring. This passive mechanism finally allows a single cohesin to accommodate two replicated DNAs (Figure 2(a)) [66]. In budding yeast, the loader becomes dispensable for cell viability when inactivated just after, but not before, G1 phase, suggesting that the cohesin loaded onto G1 chromatin is capable of cohesion establishment.…”
Section: Implications For Sister Chromatid Cohesionmentioning
confidence: 99%